Amelioration of SLE-like manifestations in (NZBxNZW)F1 mice following treatment with a peptide based on the complementarity determining region 1 of an autoantibody is associated with a down-regulation of apoptosis and of the pro-apoptotic factor JNK kinase - Rapoport, Micha J (Clinical immunology (Orlando, Fla.), 2005)
Treatment with peptides based on the complementarity determining regions (CDR) of murine and human monoclonal anti-DNA antibodies that bear the common idiotype, 16/6 Id, ameliorates disease manifestations of mice with either induced or spontaneous SLE. Aberrant expression and function of the p21Ras/MAP kinase pathway are associated with active SLE. Therefore, we examined the effect of treatment with a CDR1-based peptide of a human autoantibody (hCDR1) on the p21Ras pathway and SLE manifestations of SLE-prone (NZBxNZW)F1 mice. Untreated SLE-afflicted mice demonstrated increased expression of p21Ras and the phosphorylated active form of its down-stream element JNK kinase in conjunction with reduced hSOS and unchanged p120GAP, as compared to healthy controls. Amelioration of SLE manifestations following treatment with hCDR1 was associated with a diminished expression of phosphorylated JNK kinase, mainly in the T cell population that also exhibited reduced rates of apoptosis. Thus, hCDR1 therapy ameliorates SLE, at least in part, via down-regulation of the activity of the pro-apoptotic JNK kinase